New species of the genus Megalothorax Willem, 1900 (Collembola: Neelipleona) from a superficial subterranean habitat at Dobšinská Ice Cave, Slovakia - Papáč, Vladimír; Raschmanová, Natália; Kováč, Ľubomír (Zootaxa, 2019)
New species of Megalothorax Willem, 1900 from Dobšinská Ice Cave, Slovakia, M. dobsinensis sp. n., is described and illustrated. New species inhabits a cold habitat along an inversed temperature gradient at the cave entrance. M. dobsinensis sp. n. differs from other species of the genus by the lack of chaeta X on Ant. IV and by T-shaped inner chaetae of thoracic and abdominal sensory fields. Only two other species, M. tuberculatus Deharveng & Beruete, 1993 and M. sanctistephani Christian, 1998 lack chaeta X on Ant. IV. M. dobsinensis sp. n. differs from both species by chaetotaxy of antennae and abdomen. Summary tables of antennae and legs chaetotaxy and dichotomous identification key for species with smooth mucro are provided.